Reducing the costs of GHG estimates in agriculture to inform low emissions development: Report from an international workshop - Richards, Meryl B.; Consultative Group on International Agricultural Research; Food and Agriculture Organization of the United Nations (2014)
Sixty practitioners, policy makers and scientists reviewed and shared knowledge on the available robust and low-cost methods and data for GHG emission estimation in agriculture in a CCAFS/FAO workshop in Rome, October 2014. The participants emphasized that iterative interaction between data collection, data quality assurance and modelling is needed as well as protocol development for GHG estimation in agriculture. Emission factor development is also key, including in regional, national and sub-national levels. Easily accessible platforms where to store data and models would enhance sharing and better coordination. The country level coordination is also important in order to harmonize data collection practices, tools and methods. As countries are at different level in terms of GHG inventories and access to data, capacity need assessment will help providing right type, targeted support for capacity development. It is also important to ensure the policy level awareness raising, engagement and commitment. Linking adaptation and mitigation will reduce data needs and provide incentives for action. New tools for estimation are being developed, including remote sensing and crowd-sourcing, modeling and utilizing the national surveys and agriculture censuses that can help reduce data costs.